GENERATION X'S BELIEF IN THE LAW OF ATTRACTION (LOA) AMID THE UNCERTAINTY OF MODERN SOCIETY - Alissa Zakiah Rajabani; Tri Rini Widyastuti; Nanang Martono (Jurnal Analisa Sosiologi, 2025)
The law of attraction is a concept that some people rely on to realize their desires. The increasingly dynamic nature of modern society has led to the Law of Attraction becoming a strategy in individuals' mindsets, motivations, and behaviours, enabling them to achieve their goals. This concept is related to the self-fulfilling prophecy theory proposed by Robert K. Merton in 1948. He stated that a person's beliefs or expectations can motivate them to act in such a way that those expectations ultimately become reality. This view is also held by Generation X, who are insurance agents. This study examines insurance agents' understanding of the LoA as it is applied in their daily work. This study employed a qualitative method, conducting in-depth interviews with three informants who have worked as insurance agents at Company Z. The informants believe that their various achievements are the result of consistent LoA practice. In addition, LoA has also influenced their way of thinking and has become a mainstay of the informants when carrying out their work. This phenomenon demonstrates that believing in LoA is a rational action. However, the method of implementation is not concrete, as it relies on the influence of the subconscious, which becomes an adaptive strategy when facing life's uncertainties. This finding also shows that, amidst modernization, some individuals remain at the metaphysical stage, believing in abstract concepts such as LoA. This indicates that development towards a positive stage of society is not occurring evenly.